2017
DOI: 10.1093/nar/gkx847
|View full text |Cite
|
Sign up to set email alerts
|

FANCI and FANCD2 have common as well as independent functions during the cellular replication stress response

Abstract: Fanconi anemia (FA) is an inherited cancer predisposition syndrome characterized by cellular hypersensitivity to DNA interstrand crosslinks (ICLs). To repair these lesions, the FA proteins act in a linear hierarchy: following ICL detection on chromatin, the FA core complex monoubiquitinates and recruits the central FANCI and FANCD2 proteins that subsequently coordinate ICL removal and repair of the ensuing DNA double-stranded break by homology-dependent repair (HDR). FANCD2 also functions during the replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 76 publications
6
25
1
Order By: Relevance
“…Previous studies reported that monoubiquitination of ID2 complex may lead to dissociation of the heterodimer to its individual subunits, as measured by loss of co-immunoprecipitation of FANCI with FANCD2 (35,36). In contrast, we did not observe any Ub-mediated dissociation of ID2 in vitro.…”
Section: Monoubiquitination Locks Fanci:fancd2 On Dnacontrasting
confidence: 85%
“…Previous studies reported that monoubiquitination of ID2 complex may lead to dissociation of the heterodimer to its individual subunits, as measured by loss of co-immunoprecipitation of FANCI with FANCD2 (35,36). In contrast, we did not observe any Ub-mediated dissociation of ID2 in vitro.…”
Section: Monoubiquitination Locks Fanci:fancd2 On Dnacontrasting
confidence: 85%
“…Unlike SNPs, INDELs were more prevalent in FA than FA_RV samples, suggesting that INDELs may have continued to accumulate in the FANCD2 ‐uncorrected cell lines. FANCD2 deficiency is related to replication fork restart defects (Thompson et al, ), and stalled replication forks have been known to result in INDELs (Sankar, Wastuwidyaningtyas, Dong, Lewis, & Wang, ). However, it should be noted that this analysis does not rule out effects of other genome repair checkpoints or even side effects of cell immortalization.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Line Generation using rAAV HCT116 MCM10 +/-(exon 14) cell lines were generated using rAAV (recombinant adenoassociated virus)-mediated gene targeting (Kohli et al, 2004). The conditional vector pAAV-MCM10-cond was constructed using Golden Gate cloning and designed as described previously (Kohli et al, 2004, Thompson et al, 2017. The MCM10-cond rAAV was generated by co-transfection of pAAV-MCM10-cond, pAAV-RC (Kohli et al, 2004), and pHelper (Kohli et al, 2004) into HEK293 cells using Lipofectamine LTX (Invitrogen 15338030) following standard protocols (Kohli et al, 2004).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Targeted clones were selected using 0.5 mg/ml G418 (Geneticin G5005). Resistant clones were screened by PCR using primers within the neomycin cassette and outside the rAAV homology arms to confirm locus-specific targeting, and Cre (cyclization recombinase) transiently expressed from an adenoviral vector (AdCre; Vector Biolabs #1045) was then used to remove the neomycin selection cassette as described (Kohli et al, 2004, Thompson et al, 2017. The second round of MCM10 gene targeting used the same rAAV vector and replaced the wild type allele with a floxed allele and a downstream floxed neomycin selection cassette.…”
Section: Methods Detailsmentioning
confidence: 99%